Effect Of Sewage Sludge And Inorganic Fertilizers On Growth Performance Of Bell Pepper (Capsicum Annum Var. Nishat-1) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2018)
A field experiment was conducted in kharif 2012 and 2013 in which different  concentrations of sewage sludge alone and in combination with different  recommended doses of fertilizers (RDF) were used to assess the growth  performance of bell pepper (Capsicum annum var. Nishat-1) under Kashmir  conditions. The experiment comprised of five treatments 100% RDF; 100%  sewage sludge; 75% sewage sludge + 25% RDF; 50% sewage sludge + 50%  RDF; 50% sewage sludge + 25% RDF. Physicochemical parameters of sewage  sludge viz., pH, EC, OC, N, P, K, Ca, Mg, Cu, Fe, Mn, Zn, Cd, Ni, Cr and Pb  and pre- and post-experimental soil samples were within the permissible  limits. The highest capsicum fruit yield was found in 100% RDF treatment  (290.59 q ha-1), followed by 276.59 q ha-1 in 50% sewage sludge + 50% RDF  treatment, 246.05 q ha-1in 100% sewage sludge, 231.62 q ha-1 in 75% sewage  sludge + 25% RDF and least 222.28 q ha-1in 50% sewage sludge + 25% RDF.  Results revealed that the use of sewage sludge had no adverse impact on fruit  quality and there is an option for its use in the improvement of plant growth and soil quality thereby shall help in reducing the environmental degradation.
Keywords: Capsicum annum; fruit yield; quality; sludge; soil analysis